Cross-sectional study on the risk of breast cancer and practices among young women in Central India - Arti Tiwari; Maharaj Singh; Bharati Sahu; Shatrughan Pareek (MGM Journal of Medical Sciences)
Background: Our study focused on evaluating the risk factors associated with breast cancer among young women and highlighting the significance of early screening in this population, considering that breast cancer has the most common prevalence in women. Materials and Methods: This cross-sectional study enrolled women aged between 20 and 40 years who participated through a self-administered questionnaire. Data collection spanned 6 months, during which 250 young women were randomly recruited from different colleges in Jabalpur city, Madhya Pradesh, India. Results: Among the 250 women surveyed, 45 (18.0%) experienced early menarche and 33 (13.20%) had previously used oral contraceptives (OCP). In terms of preventive practices, 176 women (70.4%) had not engaged in breast self-examination, while 200 (80%) had not undergone clinical breast examination (CBE). However, 50 (20%) reported practicing CBE only when experiencing pain. None of the participants had undergone mammography. Regarding attitudes toward consumption of hormonal pills, 123 (49.2%) agreed that they would not take them without a prescription. Furthermore, approximately 91% did not follow weight management strategies, and 38.4% practiced meditation for stress reduction. Moreover, among the 250 young women surveyed, 218 (87.2%) did not engage in regular physical exercise (at least 3 h/week). Conclusions: While young women exhibit some risk factors for breast cancer, they often neglect appropriate preventive measures. Hence, it is recommended to commence breast cancer screening early, especially for those at elevated risk. Emphasizing awareness of breast self-examination is crucial. Moreover, launching screening programs is essential to facilitate timely detection and reduce mortality rates linked with breast cancer, especially among India’s younger female population.